(untitled) (Research, Society and Development, 2021)
Caffeine has been widely used to treat gynoid lipodystrophy (GLD). Despite caffeine has been considered as a promise treatment, there is a lack of scientific evidences regarding its effect on GLD when associated with iontophoresis or others equipment. We aimed to evaluate the effects of a caffeine gel alone and associated with iontophoresis in GLD treatment. In a single-blind randomized clinical trial, women with mild/moderate GLD in the buttocks were randomized to topical caffeine gel group (CG; n=10); caffeine gel plus iontophoresis group (CIG; n=11) or iontophoresis group (IG; n=10). The groups were treated with 10 sessions, two times/week, 20 min/session. The subjects were evaluated pre and post treatment by photonumeric GLD severity scale, ultrasound image, thermography and quality of life questionnaire with a blind evaluator. There were statistical reduction in subcutaneous tissue thickness (P≤0.046) as well as in subcutaneous tissue plus dermis thickness (P≤0.044) in buttocks both in CG and CIG. GLD reduction was similar between CG and CIG, and these reductions were more pronounced than in IG (P<0.0001). Furthermore, quality of life improved in all groups (P<0.017). We concluded that caffeine alone and associated with iontophoresis were effective for decreasing the subcutaneous fat layer in women with GLD.